Relationship of metacognitive skills, critical thinking, and students' knowledge of ecosystem concepts - Ary Indaryanti Prihatin; Ratna Komala; Rizhal Hendi Ristanto; Much Fuad Saifuddin (Universitas Ahmad Dahlan, 2022)
Metacognition and knowledge of ecosystem concepts with critical thinking is a self-learning process of critical learning toward certain objects, which are ecosystem components. The research analyzes the relationship between metacognitive skills, knowledge of ecosystem concepts, and critical thinking skills. The research is carried out at MAN 1 Tangerang from May to August 2021, involving 65 Class XI IPA-1 and XI IPA-2 students. The students are selected using a simple random sampling technique. The instrument consists of variables of metacognitive ability (X1), knowledge of ecosystem concepts (X2), and critical thinking (Y), each of which consists of 15 description questions. Thus, the total number of research samples is 195. The instrument used is an essay test that is distributed online and offline. The research method is a correlation study. The results indicate that there is no positive relationship between metacognitive skills and critical thinking with a correlation of 0.016, there is a positive relationship between knowledge of ecosystem concepts and critical thinking with a correlation of 0.490, and there is a positive and simultaneous relationship between metacognitive skills and knowledge of ecosystem concepts and critical thinking.